2013
DOI: 10.1158/1078-0432.ccr-12-2888
|View full text |Cite
|
Sign up to set email alerts
|

HIC1 Modulates Prostate Cancer Progression by Epigenetic Modification

Abstract: Purpose: Prostate cancer is the second leading cause of cancer deaths among men in Western counties, which has also occurred in Chinese male with markedly increasing incidence in recent years. Although the mechanism underlying its progression still remains unclear, epigenetic modifications are important ethological parameters. The purpose of this study is to determine the methylation status and function of hypermethylatioted in cancer 1 (HIC1) in prostate cancer progression.Experimental Design: The methylation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 31 publications
6
64
1
Order By: Relevance
“…30 In this study, we used agilent-014850 whole human genome microarrays 4 £ 44K G4112F.This Chip targets > 20,000 genes with >40000 probes originated from a broad survey of well known sources such as Ensembl, Goldenpath, RefSeq, Unigene and others. Total RNA (>300 ng) were extracted from A549/control shRNA and A549/Bmi-1shRNA cells.…”
Section: Cdna Microarray Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…30 In this study, we used agilent-014850 whole human genome microarrays 4 £ 44K G4112F.This Chip targets > 20,000 genes with >40000 probes originated from a broad survey of well known sources such as Ensembl, Goldenpath, RefSeq, Unigene and others. Total RNA (>300 ng) were extracted from A549/control shRNA and A549/Bmi-1shRNA cells.…”
Section: Cdna Microarray Analysismentioning
confidence: 99%
“…Subcutaneous tumors were established as described previously. 30 Briefly, 5-to 6-week-old BALB/c nude mice (Slaccas Laboratory Animal, Shanghai, China) were subcutaneously injected with cells (2 £ 10 6 /mouse) in PBS solution, and tumor sizes were measured every 5 day in order to calculate tumor volumes. All mice were sacrificed 5 weeks after injection.…”
Section: Experimental Tumor and Metastasis Assay In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetic alterations in cancer-related genes are recognized to play an important role in BC carcinogenesis. Epidemiological studies have consistently supported that cancer is related not only to mutations in functional genes but also related to the aberrant epigenetic modifications of various genes (Chang and Sharan, 2012;Jeong et al, 2013;Martin, 2013;Zheng et al, 2013). Altered DNA methylation profiles play crucial role in miRNAs process and this are important regulators of gene expression that are frequently deregulated in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…the level of the mRNA transcript. Zheng et al (32) analyzed the hypermethylation of HIC1 and concluded that the hypermethylation did not consistently correlate with the HIC1 expression level in breast and non-small-cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%